DEVELOPMENT OF UV-BOX CONTROL SYTEM PROTOTYPE FOR STERILIZATION MEDIA USING PHOTODIODE SENSOR - Laila Katriani; Denny Darmawan; Ahmad Awaluddin Noer (Jurnal Sains Dasar, 2015)
This research aims to design a UV box control system as sterilization media using photodiode sensor. The study began in June until November 2014. The study was conducted at the Laboratory of Electronics and Instrumentation, Department of Physics Education, State University of Yogyakarta. The design of the UV box control system consists of two stages, namely, the design of the hardware and software design. Hardware design consists of a power supply design, sensor design,  comparator design, and a buzzer. Based on the results of tests that have been done shows the power supply voltage of 4.86 volts, the reference voltage of 3.76 volts, the comparator output voltage when low of 0.12 volts, the comparator output voltage when high of 3.0 volts. Keywords: UV-Box, Sterilization Media, photodiode